(untitled) (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
Nyai Hamdanah is one of the female figures who has an important role in the history of Islam in the archipelago. Nyai Hamdana’s thoughts related to the economic sector were implemented when accompanying two pious and allamah husbands in service and da’wah. The thought of Nyai Hamdanah that has been tested can be used as a reference to give birth and produce strong and characterful sons and daughters of the nation’s generation in understanding and applying Islamic economics. Muslimah actually do not just demand equal rights, but declare the function of women for one of the economic development of Islam. The potential of women as human resources can be seen in efforts to include women’s roles in the development process starting from upstream to downstream that is sustainable, humane, moderate, tolerant, balanced, straight as well as actions that prioritize efficiency. Excluding the role of women in the development process means a waste of resources and negatively affects the pace of growth and development on all fronts; religious, educational. Social. And also in this study, the field of economics. The role of women in economic matters concenns the role of tradition and transition.